Investigation on the tectonic significance of Izmir, Uzunada Fault Zones and other tectonic elements in the Gulf of Izmir, western Turkey, using high resolution seismic data. (May 2017) - Coskun, Suleyman; Dondurur, Derman; Cifci, Gunay; Aydemir, Attila; Gungor, Talip; Drahor, Mahmut G.
Abstract: Active faults at a range in scales are observed in different directions (E-W, N-S and NE-SW) in the extensional tectonic regime of the Aegean region, western Turkey. However, mechanisms and types of faults in the Gulf of Izmir have not been investigated properly. Tectonic setting in the gulf together with the origin and characteristics of faults were studied in this study by integrating interpretation from various very high resolution acoustic data (multibeam bathymetry and CHIRP very high resolution seismic) acquired in the Gulf of Izmir. The Gulf of Izmir has thick, unconsolidated, stratified sediment cover. The water depth increases from the inner part (SE) to the outer part (NW) of the gulf with complex sea floor morphology. However, northeastern part of the coastal region is very shallow because of the sedimentary influx transported by the Gediz River. The western margin and the southern part of the gulf were formed under the influence of Uzunada (Uzun Island) and Izmir Faults, respectively. In the southern offshore, there is only one, E-W directional normal fault dipping through the north and corresponding to the offshore segment of the Izmir Fault Zone to the west. The acoustic data enable identification of the Uzunada Fault Zone extending as a simple lineament from near Guzelbahce in the south but bifurcating toward the NE of the Cicek Archipelago and terminating with left-lateral slip in the E-NE of the Hekim Island. After the sinistral strike-slip, the fault re-extends in the NW direction untill the mid of Uzunada as a single fault segment. Then, the fault is observed as a bunch of many active fault segments (like horse-tail splays) to the east of Uzunada with N-NW elongation through the outer gulf. These segments were chronologically succeeded from the east to the west. This progradational pattern is attributed to westward extension of the Gulf of Izmir with anti-clockwise rotational escape of the Anatolian Plate. In addition, progradation of faults was controlled by the NE-SW directional tear faults which may have played a key role in the shoreline extension and general pattern of the outer gulf islands. A very young graben in the central part of the gulf, also dislocated by the tear faults was observed parallel to the Uzunada Fault Zone as another indicator of ongoing fan-shaped opening of the gulf. These tectonic elements are consistent with earlier interpretation of GPS-based observations indicating a four-wheel gear system of rigid-body rotations. Additionally, a new fault extending from the far offshore of Foca to Suzbeyli village to the south was identified in this study. Its NW-SE extension is angular to the previous tectonic elements. All these elements apparently project at least 10 km farther northward, in the offshore Foca where the earthquake epicenters cluster. Highlights: Multibeam echosounder and CHIRP seismic data are used to identify offshore faults. In the southern offshore, there is only, E-W directional normal fault (Izmir Fault). Uzunada Fault splits into many segments, controlled by the tear faults. An active graben in the gulf was observed parallel to the Uzunada Fault Zone. Another offshore fault (named Foca-Suzbeyli) is defined for the first time.